The protective effects of red beetroot (Beta vulgaris l.) against oxidative stress in rats induced by high fat and fructose diet - Dianandha Septiana Rubi; Abrory Agus Cahya Pramana; Sunarti (Acta Biochimica Indonesiana, 2020)
Background: One of consequence high-fat and fructose diet is oxidative stress. Consumption of antioxidants from red beetroot may increase antioxidant defense. Objectives: This study aimed to evaluate red beetroot administration on improving antioxidant defense in rats induced high fat and fructose diet. Methods: A total 20 male Wistar rats were divided into 4 groups: 1) normal control group (N), received standard diet; 2) High fat and fructose diet (HF), received high fat and fructose diet (HFFD); 8 weeks induction with HFFD and received 9g red beetroot (BA); and combination of HFFD and 9g of red beetroot from beginning of the study (HFBA). At the end of the study the levels of circulatory oxidized LDL (ox-LDL) were determined using enzyme-linked immunosorbent assay (ELISA) method. Superoxide dismutase 2 (SOD2) and catalase (CAT) gene expressions were determined by quantitative polymerase chain reaction (qPCR) method. Results: Induction HFFD increased the levels of circulatory ox-LDL levels compared to normal control (10.00±0.29 vs 12.69±0.57). Administration of red beetroot for 6 weeks and combination HFFD with red beetroot during the study significantly decreased ox-LDL levels compared to high fat and fructose group (12.69±0.57 vs 9.66±0.46) and (12.69±0.57 vs 8.59±0.18), respectively. The decreased circulatory ox-LDL levels were found negatively correlated with upregulation SOD2 (r=-0.548; P=0.012) and CAT (r=-0.460; P=0.041) gene expression in the liver tissues. Conclusion: Administration of red beetroot may ameliorate oxidative stress in rats induced high-fat and fructose diet through increasing antioxidant defense.